Glycol chitosan functionalized asenapine nanostructured lipid carriers for targeted brain delivery: Pharmacokinetic and teratogenic assessment - Singh S.K.; Hidau M.K.; Gautam S.; Gupta K.; Singh K.P.; Singh S.K.; Singh S. (My University, 2025)
Blood brain barrier (BBB) is a complex, tight barrier between endothelial cells of cerebral blood vessels. It acts as a physical barrier and provides access to only those moieties which are necessary for proper brain functioning. However, this selective prudence also acts as a hindrance in therapeutic targeting of brain necessitating pharmaceutical intervention. Intranasal drug delivery is one such approach which we have exploited here for targeted brain delivery of asenapine by glycol chitosan coated nanostructured lipid carrier (GC-ANLC). The best formulation was characterized for particle size (184.2 ± 5.59 nm), zeta potential (18.83 ± 1.18 mV), entrapment efficiency (83.52 ± 2.59%) and surface morphology (spherical and smooth). In-vitro drug-release study showed that Higuchi model (r2 = 0.9938, AIC = 52.94) dictated asenapine release from GC-ANLC. Cell compatibility study suggested biocompatibility of GC-ANLC with A549 cell line as well as nasal epithelial cell membrane. After intranasal delivery, Charles-Foster rats demonstrated approximately 2.3 and 4 fold higher systemic and brain bioavailability of GC-ANLC compared to asenapine solution (ASM). Embryo fetal toxicity study was further conducted to investigate the teratogenic effect of GC-ANLC. In conclusion, prepared GC-ANLC could be used as a promising drug carrier for delivery of asenapine via intranasal route with better pharmacokinetic and safety profile. © 2017 Elsevier B.V.